The Effect of Quality Sexuality Health Education Using the Strategy Method on Knowledge of the Dangers of Pre-Marital Sex in Adolescent Students - Fani Fionita; Rahmawati Rahmawati; Rismanudin Rismanudin (GLOBAL HEALTH SCIENCE GROUP, 2026)
Adolescent sexual behavior in Indonesia shows an increasingly worrying trend, as evidenced by the rise in premarital sex, unwanted pregnancies, abortions, and early marriages. This phenomenon reflects the vulnerability of adolescents in facing biological, psychological, and social changes that are not balanced with adequate knowledge and attitudes. The influence of social environments, media exposure, and weak internalization of moral values also increase the risk of unhealthy sexual behavior. These conditions indicate that existing prevention efforts have not been able to comprehensively address the needs of adolescents. Therefore, this research is important to gain a deeper understanding of the factors that influence adolescent sexual behavior and to serve as a basis for formulating more effective, sustainable, and culturally appropriate educational and intervention strategies. This study aimed to determine the effect of health education using the stratagem method on students' knowledge of the dangers of premarital sex at SMPN 3 Bontomarannu. This was done by assessing their knowledge levels before and after the intervention. The results showed an increase in adolescents' understanding after the intervention, indicating that the stratagem method was effective in increasing their knowledge. This study applied a quantitative approach with an experimental design aimed at determining the causal relationship between variables through manipulation of independent variables. The study population included individuals who met the predetermined inclusion criteria and were relevant to the study objectives. There were 44 respondents in this study, divided into 22 respondents in the intervention group and 22 respondents in the control group. This study demonstrates that sexuality education using the staging method effectively improves students' understanding of the risks of premarital sex. Involving 44 respondents through simple random sampling, pre- and post-test results showed a significant increase in the intervention group compared to the control group. The results of the study showed that before the intervention there was no difference in knowledge between the two groups, but after being given counseling on the stratagem method, the intervention group experienced a significant increase, while the control group did not show any significant changes.